Multi-Dimensional Strategic Model to Enhance Institutional Performance Under Digital Transformation: An Applied Framework in the Saudi Context - Almutairi, Mona Jeza; Alhallafi, Hassan Khidhr; Alabbas, Almotasim Khalil (Journal of Economic, Administrative and Legal Sciences, 2025)
The Saudi context, under the Kingdom’s Vision 2030, is witnessing rapid digital transformations aimed at building an integrated digital economy and enhancing institutional performance across various sectors. Despite these efforts, there remains a clear gap in applied models that integratively link digital leadership, digital transformation technologies, and institutional performance measurement systems. Most previous studies have addressed these dimensions separately, resulting in the absence of a comprehensive strategic framework capable of achieving the required functional integration to sustain digital transformation. Accordingly, this study gains its importance by proposing a multidimensional strategic framework that addresses this research and practical gap, enhancing the ability of Saudi institutions to adapt to rapid environmental and technological changes while contributing to sustainable development and national strategic goals. The study sought to develop a unified strategic model based on integrating three main pillars: digital leadership, performance measurement systems, and emerging technologies, within a functional framework that promotes institutional digital maturity. The study was guided by several main hypotheses, most notably: the existence of a statistically significant positive relationship between digital leadership and institutional performance improvement; a positive relationship between adopting modern technologies and the efficiency of administrative processes; and an interactive hypothesis stating that integrating these three dimensions would enhance institutional performance more significantly than the impact of each dimension separately. A descriptive-analytical methodology was employed, relying on a review of recent literature and official performance reports from Saudi governmental institutions to contextualize the findings within the national digital transformation framework. The results revealed weak coordination among digital infrastructure components, limiting the achievement of the required strategic coherence.
Keywords: Digital transformation; Digital leadership; Institutional performance; Emerging technologies; Artificial inteligence; Strategic framework; Vision 2030